Convergent phenotypic evolution of the visual system via different molecular routes: How Neotropical cichlid fishes adapt to novel light environments. Issue 4 (17th July 2018) - Härer, Andreas; Meyer, Axel; Torres‐Dowdall, Julián
Abstract: How predictable is evolution? This remains a fundamental but contested issue in evolutionary biology. When independent lineages colonize the same environment, we are presented with a natural experiment that allows us to ask if genetic and ecological differences promote species‐specific evolutionary outcomes or whether species phenotypically evolve in a convergent manner in response to shared selection pressures. If so, are the molecular mechanisms underlying phenotypic convergence the same? In Nicaragua, seven species of cichlid fishes concurrently colonized two novel photic environments. Hence, their visual system represents a compelling model to address these questions, particularly since the adaptive value of phenotypic changes is well‐understood. By analyzing retinal transcriptomes, we found that differential expression of genes responsible for color vision (cone opsins and cyp27c1 ) produced rapid and mostly convergent changes of predicted visual sensitivities. Notably, these changes occurred in the same direction in all species although there were differences in underlying gene expression patterns illustrating nonconvergence at the molecular level. Adaptive phenotypes evolved deterministically, even when species differ substantially in ecology and genetic variation. This provides strong evidence that phenotypic evolution of the visual system occurred in response to similar selective forces of the photic environment.